Study of the confinement performance and stress-strain response of RC columns with corroded stirrups. (1st September 2022) - Zhang, Qin; Zheng, Nai-Hao; Gu, Xiang-Lin; Wei, Zong-Yan; Zhang, Zheng
Highlights: Confinement behavior of concrete columns with corroded stirrup was investigated. Confinement performance for considering the effects of synchronized corrosion of the stirrups and longitudinal reinforcements was studied. Effect of stirrup spacing and size effect on constraint behavior was emphasized. Optimal stress–strain model of concrete confined with corroded rebar was proposed. Abstract: In this paper, the confinement performance and stress–strain response of reinforced concrete (RC) with corroded reinforcement were studied, with consideration given to such key parameters as corrosion levels, size effect, stirrup configurations, and effects of synchronized corrosion of the stirrups and longitudinal reinforcements. A total of 29 square RC columns, which had been corroded through accelerated corrosion tests, were examined using axial compression evaluations. The theoretical corrosion levels of the stirrups ranged from 0% to 20%. The column size coefficient (defined as the volume ratio of the corroded columns to the standard prism) varied from 1.0 to 4.17, and the spacings of the stirrups ranged between 50 mm and 125 mm. The test results revealed that the confinement behaviors were significantly affected by the severity of the corrosion of the stirrups, including the failure mode, bearing capacity, and deformability. The highest reductions in load and displacement ductility were found at a theoretical corrosion level of 20%, up to 22.37% and 77.05%, respectively. Meanwhile, the confinement performance was also found to be influenced by the stirrup spacings and specimen sizes. It was found that although the corrosion of stirrup was much higher than that of longitudinal reinforcement, the corrosion of longitudinal reinforcement would still less affect the compressive performance of the RC column. The semiempirical and semi-theoretical formulas for calculating the compressive strength and corresponding strain were proposed based on the experimental data and theoretical analysis results. Then, an optimal stress–strain prediction model for concrete confined with corroded stirrups was successfully established. The proposed model showed a good correlation with the experimental data when compared with the existing prediction model.